(untitled) (Balneo and PRM Research Journal, 2021)
Introduction. Brachial plexus lesions vary in severity, depending on the etiopathogenic mechanism and the level of force to which the plexus is exposed. In the same patient, several nerves of the plexus can be damaged in varying degrees of severity. Brachial plexus injuries lead to upper limb paralysis and disability. Material and Methods. We present the case of a 68-year-old woman diagnosed a year ago with multiple myeloma, clavicular plasmacytoma and secondary spontaneous clavicle fracture. At the same time she presented several dislocations of the shoulder and was diagnosed with brachial plexus palsy after the last dislocation. The patient was hospitalized in our department with a large motor deficit in the upper limb. A comprehensive motor rehabilitation program has been established three weeksafter installing the palsy. Results and discussion. The evolution of the patient was favorable. It was noticed the reduction of the symptoms and slight improvement in motor deficit of the affected upper limb. Thepatient rehabilitation should continue for several months because the nerve regenerates slowly. Conclusion. In patients with brachial plexus injury, motor rehabilitation should be instituted as early as possible and continued for a longer periodoftime until nerve regeneration occurs.It results that early and continuous medical rehabilitation is essential in patients with brachial plexus injury.